Collaborative practices between correctional and mental health services in Norway: Expanding the roles and responsibility competence domain. Issue 1 (2nd January 2017) - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle
ABSTRACT: Internationally, mental illness is high in prison populations. Collaboration between the correctional services (CS) and mental health services (MHS) is required to address this. Little is known of the collaborative processes in this context, however. This article presents the findings of a study exploring the characteristics of collaborative practices between the MHS and CS in a Norwegian context. A purposeful sample ( n = 12) of MHS and CS leaders was recruited from one region in Norway. Taking a generic qualitative approach, semi-structured interviews with each participant explored specific structures that promoted collaboration, the nature of collaborative relationships, and factors that facilitated or constrained these. The study indicated that leaders are exercised by one dimension of collaborative practice in particular, namely the distribution of responsibility for the care of the offender across systems. This activity is mediated by highly complex external structures as well as the individual characteristics of the professionals involved. They speculate that professionals and organisations who fail to take responsibility for the offender as expected may be constrained from doing so by resource limitations, logistical issues, and poor attitudes towards the offender population. Based on these findings, this study suggests that the MHS and CS workforce would benefit from a great knowledgeability of the roles and responsibility domains of collaborative practice. Improving competence in the workforce in this area would achieve this. However, competency frameworks that address this domain are currently limited. Recommendations on how to extend the remit of this domain in light of the current findings are provided.